Behavior of eukaryotic symbionts in large benthic foraminifers Calcarina gaudichaudii and Baculogypsina sphaerulata under exposure to wastewater. (October 2020) - Akther, Shumona; Suzuki, Jumpei; Pokhrel, Preeti; Okada, Teruhisa; Imamura, Masahiro; Enomoto, Tadao; Kitano, Takashi; Kuwahara, Yuji; Fujita, Masafumi
Abstract: Large benthic foraminifers (LBFs) are significant contributors to coral island formation in the Pacific Ocean. In recent years, the population of LBFs has decreased because of the increase in anthropogenic influences, such as wastewater (WW) discharge. To implement efficient mitigation measures, pollution tolerance in LBFs should be understood. However, the effects of WW on LBFs and their symbionts have not yet been demonstrated. This study examined the changes in the photosynthetic efficiency ( Y [II]) of Calcarina gaudichaudii and Baculogypsina sphaerulata in response to WW by using a pulse-amplitude-modulation fluorometer. These LBFs were exposed to WW with different dilution levels for 22 days. The Y (II) values of the LBFs were found to deteriorate within 1–2 days. However, the Y (II) values both deteriorated and were enhanced in the experiments, thus indicating that WW contains both harmful and beneficial components. Baculogypsina sphaerulata showed an earlier response and greater sensitivity to WW and a higher epibiont infestation than C. gaudichaudii . This result can be attributed to the differences in the physiological and morphological responses of distinct LBFs. A sequencing analysis of 18S rDNA confirmed that the dominant eukaryotic symbionts in the two LBFs studied were Ochrophyta and Labyrinthulomycetes. These eukaryotic symbionts were released and attached as epibionts onto LBFs that were exposed to WW, thus leading to an increase in inactive LBFs. The Shannon–Weaver and Simpson diversity indices revealed that eukaryotic symbiont communities decreased in biodiversity after exposure to WW because of the abundance of algal symbionts. On the basis of these results, we conclude that WW, even with 10, 000 × dilution, causes a decrease in active LBF populations owing to the release of eukaryotic symbionts, the decrease in biodiversity, and the infestation of epibionts even though Y (II) is temporarily enhanced. These responses are more significant in B. sphaerulata than in C . gaudichaudii . Graphical abstract: Image 1 Highlights: Wastewater deteriorates or enhances photosynthetic efficiency. Baculogypsina spp. is more sensitive to wastewater than Calcarina spp. The dominant eukaryotic symbionts are Ochrophyta and Labyrinthulomycetes. Epibiont infestation occurs owing to symbiont release. Exposure to wastewater decreases the diversity of eukaryotic symbionts. Abstract : WW decreases the active LBFs owing to the release of eukaryotic symbionts, although Y (II) temporarily increases, their biodiversity decreases, and epibiont infestation occurs.